Термічні перетворення пірогенного кремнезему, модифікованого оксидом міді - Oranska, O. I. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
Structural transformations of silica matrix in the nanocomposites and mechanical mixtures based on fumed silica and copper oxide, CuO, were studied by means of X-ray diffraction and thermal analysis. Effect of copper oxide on the temperature of crystallization of silica, the diversity of its crystalline modifications and their relationship depending on the specific surface of fumed silica was shown.